Pengaruh Penggunaan Plastik Polyethylene (Pe) Dan High Density Polyethylene (Hdpe) Pada Campuran Lataston-Wc Terhadap Karakteristik Marshall - Rahmawati, Anita (Semesta Teknika, 2015)
The increase in road traffic during the last two decades in combination with an insufficient degree of maintenance due to shortage in funds has caused an accelerated and continuous deterioration of the road network. To alleviate this process, several types of measures may be effective, e.g., securing funds for maintenance, improved roadway design, use of better quality of materials and the use of more effective construction methods. Aspalt can also be modified by adding different types of additive. One of these additives is the polymers such as Polyethylene (PE) and High Density Polyethylene (HDPE). The addition of polymers typically increases the stiffness of the aspalt and improves its temperaturesusceptibility. Increased stiffness improves the rutting resistance of the mixture in hot climates and allows the use of relatively softer base aspalt, which in turn,provides better low temperature performance. This study was conducted to determine the effect of utilizing Polyethylene (PE) and High Density Polyethylene (HDPE) as a mixture of thin layer of asphalt concrete in wearing course (Lataston_WC) using Marshall design parameters. The parameters assessed are the stability, flow, the percentage of air void in the mixture (VIM), the percentage of void in the mineral aggregate (VMA), the percentage of void filled with aspalt (VFA), and Marshall Quotient (MQ). Marshall samplers prepared with the PE and HDPE modified aspalt binder provide the specification limits. The percentage of PE and HDPE as asphalt mixture is 0%, 2%, 4% and 6% by weight of the asphalt. The result of Marshall test showed that the value of stability, flow and VFA have tendencey to increase with incresing of percentage of PE and HDPE. But, the value of VIM, VMA and MQ have tendency to decrease with incresing of percentage of PE and HDPE. It can be seen that effect of addition HDPE on aspalt mixture provide the value of Marshall characteriscs are better than aspalt mixture with PE